TNF-α Antagonist and Infection in Rheumatoid Arthritis - Simard, Julia F. (2012)
BACKGROUND: Anti-TNF treatment may increase infection risk, although this has been difficult to study because the timing of anti-TNF treatment is driven by disease activity, which may influence infection susceptibility leading to confounding that varies over time. We evaluated the association between anti-TNF initiation in rheumatoid arthritis (RA) patients on disease modifying anti-rheumatic drugs (DMARD) and infection using multiple approaches adjusting for time-varying confounding. METHODS: 383 anti-TNF-naïve RA patients on ≥1 non-biologic-DMARD at enrollment from the Brigham and Women's Rheumatoid Arthritis Sequential Study (BRASS) were followed up to two years. Pooled logistic regressions estimated the association between anti-TNF and infection by including time-varying covariates in the adjusted models and inverse probability treatment weighting (IPTW). RESULTS: Adjustment for time-varying disease activity and other suspected confounders yielded non-statistically significant positive associations between anti-TNF start and infection regardless of analytic approach (RR(mvar_adj) = 2.1, 95% CI: 0.8 – 5.8). CONCLUSIONS: Incorporating changing clinical status, and treatment indications and consequences, yielded consistently (though not significantly) elevated relative risks of infection associated with anti-TNF initiation. Due to limited statistical power, we cannot draw firm conclusions. However, we have illustrated multiple approaches adjusting for potential time-varying confounding in longitudinal studies and hope to replicate the approaches in larger studies.